2010
DOI: 10.1177/0907568210369219
|View full text |Cite
|
Sign up to set email alerts
|

Progressing children’s participation: Exploring the potential of a dialogical turn

Abstract: Children’s participation is increasingly ambiguous and contested. Such complexity emerges in response to its emancipatory possibilities as well as unresolved tensions and power practices. The authors argue that closer attention must now be given to the interpretative milieu of children’s participation, that is, to the act of dialogue that has emerged as central to the participatory process. They point to the need for a critical examination of dialogue in facilitating and resisting the recognition of children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 28 publications
(17 reference statements)
1
77
0
3
Order By: Relevance
“…In order to more fully recognize children, Graham and Fitzgerald (2010) add that a 'dialogue approach' holds potential. Similarly to Gallacher and Gallagher's (2008) concept of 'methodological immaturity', they explain that, firstly, through dialogue adults are ontologically forced to consider how they understand the nature of dialogue itself.…”
Section: Discussionmentioning
confidence: 99%
“…In order to more fully recognize children, Graham and Fitzgerald (2010) add that a 'dialogue approach' holds potential. Similarly to Gallacher and Gallagher's (2008) concept of 'methodological immaturity', they explain that, firstly, through dialogue adults are ontologically forced to consider how they understand the nature of dialogue itself.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a need to conceptualize participation as a dialogic encounter has been expressed, promoting a shift from listening to children to establishing dialogues in research (Cooper, Nazzari, Kon Kam King, & Pettigrew, 2013;Graham & Fitzgerald, 2010;Neale, 2002), while considering children's views on participative research methods (Hill, 2006;Warming, 2011). Furthermore, research phases that are especially challenging with regard to children's participation have been identified.…”
Section: Photo Interviews In Research With Childrenmentioning
confidence: 99%
“…To paraphrase Graham and Fitzgerald (2010), in order to work with the power practices within and around participation, networks of power need to be identified and understood. In policy research we found that power and decision-making are intertwined and exist in a grey area mostly influenced by the distribution of power shared between peers and across generations.…”
Section: Dr Darren Sharpementioning
confidence: 99%